COPYRIGHT PROTECTION SYSTEM BASED WATERMARKING - ZEEBAREE, IMAD MAJED; ABDULLAH, HIWA ALI; KHALIFA, FARHAD M.; KAREEM, OMER SEDQI (Journal of Duhok University, 2023)
In digital information science, there is a crisis represented in resisting tampering and protecting the copyright of digital content when storing, transmitting, and processing encrypted information in systems where digital content can easily be disseminated through communication channels. Watermarking is one of the techniques adopted in protecting digital property and information. It is the technology of infusing a watermark with property rights in other multimedia through a specific algorithm. A comparison of the two digital watermarking methods known as DWT and DWT-SVD is offered in this article. In the case of using the watermark technique with DWT wavelet transformation, the decomposition of the original image is complete for the watermark implant, and in the case of the DWT-SVD watermark technique the original image given to the DWT is first decomposed and then the watermark is transplanted into the individual values obtained by applying SVD (single value analysis). Watermarking methods in this work aim to provide protection for copywriting. Later, presentations of the presented technologies are compared based on PSNR and MSE values. The results show that the hybrid DWT-SVD technique is significantly better than the DWT technique. Finally, the proposed method has been compared with another watermarking technique. The system is also very resistant to a variety of image-processing-related attacks